Formulasi Pengembangan Usaha Keripik Daria Melalui Pendampingan Digital Marketing Menggunakan Metode ABCD (Asset Based Cummunity Development) di Desa Pesawahan Kecamatan Tiris - Batu Bara, Eka Elviana; Ghafur , Abd. (Najah: Journal of Research and Community Service, 2025)
Coffee plantations are one of the products of natural resources from the plantation and agriculture sectors. The purpose of the service is to optimize the cultivation and production of grafted coffee plants through assistance with the ABCD (Asset Based Community Development) approach in Ranugedang Village, specifically in Ledduk Hamlet. The results of the people's coffee plantations are the main commodity, and a source of livelihood for the majority of people in Ranugedang Village, especially in the village of Ledduk. Therefore for growth and for optimal production it is necessary to consider the suitability of the soil and the growth requirements of each plant species, especially coffee, which we will discuss next. In this study the authors used the Asset Based Community Development (ABCD) approach in identifying and mobilizing assets. ABCD is an approach to community development that is in a big stream trying to realize a social life order in which the community becomes the actor and determinant of development efforts in their environment, while the process of implementing the program is divided into 5 (five) stages, namely Discovery (Assessment), Dream (Dream), Design (Procedure), Define (Goal), Destiny (Self Determination). Data collection was carried out using the field study method by conducting interviews with local residents. The results of the service carried out is the facilitation of the community on their own will and dedication, especially coffee farmers in optimizing the cultivation and production of grafted coffee plants. additional knowledge from the internet and credible references.